Doheny Towers, preliminary drawings [cover sheet] - Victor Gruen Associates::::::::: (1959)
Cover sheet for coordinator's set of preliminary drawings for Doheny Towers in Los Angeles, California. The building was constructed near the intersection of Doheny and Sunset Boulevard.